Physicochemical Characteristic of Fermented Goat Milk Added with Different Starters Lactic Acid Bacteria (Faculty of Animal Science Universitas Brawijaya, 2018)
Development of traditional food including dadih to be commercial fermented milk was needed to achieve efficiency and effective of products. Dadih with natural starter needs to be changed with starters because starters can be produced commercially. This study aims to evaluate physicochemical characteristic of fermented goat milk that added with different starters Lactic Acid Bacteria (LAB) isolated from dadih. The materials used for this research were starters LAB that isolated from dadih. In this experiment, treatments were used different starters that namely starter 11, starter 21, starter 25, starter 29, and starter 41 then analized about water content, ash content, fat content, syneresis, and viscosity. The experiment was carried out with three replications. The data were analyzed by ANOVA using the basic design of Completely Randomized Design (CRD) and continued by Duncan's Multiple Range Test (DMRT) if there was a significantly different. The results showed that different starters had influence on water content, ash content, fat content, syneresis, and viscosity. It could be concluded that starters 11 and 41 were the best starter that can be applied in fermented goat milk product based on physical quality with lower syneresis and higher viscosity. But based on chemical quality, starter 11 was the best starter with lower water content and higher ash content.